Relationship between occupational exposure to whole-body vibration and noise with sex hormone levels: An empirical assessment in an automobile parts manufacturing plant. (July 2021) - Mohammadi, Hamzeh; Golbabaei, Farideh; Dehghan, Somayeh Farhang; Ardakani, Soheila Khodakarim; Imani, Hossein; Tehrani, Fahimeh Ramezani
The present study investigated the relationship between occupational exposure to noise and whole-body vibration (WBV) with the levels of sex hormones in an automobile parts manufacturing plant. The level of workers' exposure ( n = 162) to each of the mentioned stressors was measured through standard methods, and the time-weighted average of exposure was calculated for each person. In order to determine serum sex hormones (free testosterone, luteinizing hormone, and follicle-stimulating hormone), blood samples were taken from all participants after 8–10 h of fasting between 7 and 9 am and then the blood samples were analyzed by an enzyme-linked immunosorbent assay method. In general, regarding testosterone as the main male sex hormone, only 49% of the participants were in the normal range. In a total of three sections, the lowest mean testosterone levels were observed in the third exposure group (WBV > 1.93 m/s 2 ; noise >92.69 dB) of the studied stressor; however, only the difference in testosterone levels between the three different groups of exposure to noise was statistically significant ( p = 0.001). The relationship between demographic variables and levels of noise and WBV exposure with sex hormones was not linear and only the relationship between noise exposure and testosterone levels was statistically significant ( R = −0.201, p = 0.013). According to the results of logistic regression, the WBV had the greatest effect on testosterone levels. However, according to the results of the correlation test, only the relationship between noise exposure and testosterone levels was statistically significant.